The Acyl Desaturase CER17 Is Involved in Producing Wax Unsaturated Primary Alcohols and Cutin Monomers. Issue 2 (9th January 2017) - Yang, Xianpeng; Zhao, Huayan; Kosma, Dylan K.; Tomasi, Pernell; Dyer, John M.; Li, Rongjun; Liu, Xiulin; Wang, Zhouya; Parsons, Eugene P.; Jenks, Matthew A.; Lü, Shiyou
Abstract : CER17/ADS4 is involved in unsaturated wax and cutin monomer production in Arabidopsis. Abstract: We report n -6 monounsaturated primary alcohols (C26:1, C28:1, and C30:1 homologs) in the cuticular waxes of Arabidopsis ( Arabidopsis thaliana ) inflorescence stem, a class of wax not previously reported in Arabidopsis. The Arabidopsis cer17 mutant was completely deficient in these monounsaturated alcohols, and CER17 was found to encode a predicted ACYL-COENZYME A DESATURASE LIKE4 (ADS4). Studies of the Arabidopsis cer4 mutant and yeast variously expressing CER4 (a predicted fatty acyl-CoA reductase) with CER17/ADS4, demonstrated CER4 's principal role in synthesis of these monounsaturated alcohols. Besides unsaturated alcohol deficiency, cer17 mutants exhibited a thickened and irregular cuticle ultrastructure and increased amounts of cutin monomers. Although unsaturated alcohols were absent throughout the cer17 stem, the mutation's effects on cutin monomers and cuticle ultrastructure were much more severe in distal than basal stems, consistent with observations that the CER17/ADS4 transcript was much more abundant in distal than basal stems. Furthermore, distal but not basal stems of a double mutant deficient for both CER17/ADS4 and LONG-CHAIN ACYL-COA SYNTHETASE1 produced even more cutin monomers and a thicker and more disorganized cuticle ultrastructure and higher cuticle permeability than observed for wild type or either mutant parent, indicating a dramatic genetic interaction on conversion of very long chain acyl-CoA precursors. These results provide evidence that CER17/ADS4 performs n -6 desaturation of very long chain acyl-CoAs in both distal and basal stems and has a major function associated with governing cutin monomer amounts primarily in the distal segments of the inflorescence stem.